Phase equilibrium diagram of the Y–Dy–Ge system at 870 K - Shpyrka , Z.; Staskevych, Z.; Horyn, A.; Pavlyuk, V. (Physics and Chemistry of Solid State, 2025)
The interaction of the components in the Y–Dy–Ge ternary system was investigated using the methods of X-ray phase analysis, microstructure and energy dispersive X-ray spectroscopy in the whole concentration range at temperature of 870 K. The existence of continuous solid solutions of substitution with the AlB2 (Y1-xDyxGe1.5), Y3Ge5 (Y3-xDyxGe5), CrB (Y1-xDyxGe), Ho11Ge10 (Y11-xDyxGe10), Sm5Ge4 (Y5-xDyxGe4) and Mn5Si3 (Y5-xDyxGe3) structure types was found. Limited solid solutions of the substitution type, based on the binary compounds YGe1,82 (0.20 at. part Dy), YGe2 ( 0,10 at. part Dy), DyGe1,9 (0.07 at. part Y) and DyGe1,85 (0.05 at. part Y) were observed. The electrical and magnetic properties of the Y5Dy30Ge65 (DyGe1,85 structure type) and (YGe1,82 structure type) alloys were studied. The phase Y30Dy5Ge65 is Curie-Weiss paramagnet in the investigated temperature range. On the thermogram of the Y10Dy20Ge65 alloy during cooling, we observe an intense peak at temperature of 1207.4 K (at maximum), the thermal effect of which reflects the formation of the Dy1-xYxGe1.85 phase.